Students' Conceptual Understanding In Terms Of Gender Differences - Azizah, Nurul; Budiyono, Budiyono; Siswanto, Siswanto (Universitas Sebelas Maret, 2021)
One of the basic skills that students must master to learn mathematics is conceptual understanding. Gender differences have an influence on the disparity level of students' conceptual understanding. This research is qualitative descriptive research that aimed to analyze the students' conceptual understanding in solving set problems in terms of gender differences. The research subjects were 9th-grade students of SMP N 3 Surakarta. The concept understanding ability test was used as a research instrument. The results showed that male students had an excellent conceptual understanding in applying concepts in mathematical calculations and translating images into other forms of interpretation, 2) Female students had a fairly good conceptual understanding in translating images into other forms of interpretation, although female students tend to be weak in determining the right concepts to be used in solving problems and applying concepts in mathematical calculations.